STUDI DESKRIPTIF TENTANG PERUBAHAN PSIKOLOGIS PADA IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS LAWANG KABUPATEN MALANG - Prahesty Yuliawardani; Tri Nataliswati; Tutik Herawati; Budiono (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
The most prominent change in the third trimester in pregnant women is psychological changes. Trimester III is a phase called the waiting or vigilant period because pregnant women cannot wait for the birth of their babies. In this period, psychological changes that arise are fear, worry if the baby is born abnormally, fear of pain in the process of labor and fear of not being able to take care of the baby. Multigravida mothers, naturally also experience psychological disorders in the form of anxiety about the shadow of the pain she suffered in the past during childbirth. Especially for mothers who have experience with high-risk pregnancies, the anxiety level must also increase. Where this pregnancy has a high risk both during pregnancy and in the process of labor. There are also mothers who have experienced traumatic experiences and this has been shown to affect the anxiety of pregnant women in facing labor. The purpose of this study was to determine psychological changes in third trimester pregnant women in the Lawang Health Center Working Area. The design in this study was descriptive with a cross sectional approach. The population was 34 and the sample was also taken 34 people using the total sampling technique. The instrument used in this study was a questionnaire with a closed interview method. Research result shows that on average (71%), their psychological change is quite good. The conclusion of this research result is that the average pregnant women doesn’t know about psychological change and this can be resolved with giving counseling about pregnancy. Hopefully when they’re checking their pregnancies in Health Center, pregnant women would reach out and talk about their complaint or public opinion, especially primigravida women in their third trimester, so it can decrease their worry about their fetus.